Identification of potential functions of polo-like kinase 1 in male reproductive development of the oriental river prawn (Macrobrachium nipponense) by RNA interference analysis - Jin, Shubo; Zhang, Wenyi; Wang, Pengchao; Jiang, Sufei; Qiao, Hui; Gong, Yongsheng; Wu, Yan; Xiong, Yiwei; Fu, Hongtuo (Frontiers in Endocrinology, 2022)
Polo-like kinase 1 (Plk1) has multiple functions in the cell cycle, including in the maturation of centrosomes during the G2/M transition, the separation of centrosomes, and the activation of cyclin-dependent kinase 1 expression and spindle assembly. In this study, we investigated the potential regulatory roles of Plk1 in the reproductive development of the male oriental river prawn (Machrobrachium nipponense). The full cDNA sequence of Mn-Plk1 was 2360 base pairs long, with an open reading frame of 1836 base pairs encoding 611 amino acids. Protein sequence alignment identified a conserved serine/threonine kinase domain and two Polo-boxes. Phylogenetic tree analysis revealed that Mn-Plk1 had the closest evolutionary distance with Plk1s of freshwater prawns and then with those of crustacean species, whereas the evolutionary distance with mollusks was much more distant. Quantitative PCR analysis predicted that Mn-Plk1 plays essential roles in the regulation of gonad development. RNA interference analysis and histological observations showed that expression of insulin-like androgenic gland hormone decreased as the expression of Mn-Plk1 decreased, and fewer than 5% of cells were sperm cells at day 14 in the dsPlk1 injected prawns. This result indicated that Plk1 positively regulated testis development in M. nipponense by affecting the expression of this hormone. Our results highlight the functions of Plk1 in M. nipponense and provide valuable information that can be applied to establish artificial techniques to regulate testis development in this species.